2021
DOI: 10.1101/2021.01.28.428679
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inference of an integrative, executable network for Rheumatoid Arthritis combining data-driven machine learning approaches and a state-of-the-art mechanistic disease map

Abstract: MotivationRheumatoid arthritis (RA) is a multifactorial autoimmune disease that causes chronic inflammation of the joints. RA is considered a complex disease as it involves various genetic, environmental, and epigenetic factors. Systems biology approaches provide the means to study complex diseases by integrating different layers of biological information. Combining multiple data types can help compensate for missing or conflicting information and limit the possibility of false positives. In this approach, we … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…Indeed, in our modelling framework, all results with anti-TNF drugs were inadequate to entirely suppress the inflammation phenotype, suggesting that blocking TNF alone is insufficient to hamper the signal. Our results also follow the findings of (Miagoux et al , 2021), which demonstrated that IL6 suppression was more successful in downregulating key transcription factors leading to inflammation in patients treated with anti-TNF treatment.…”
Section: Resultssupporting
confidence: 90%
“…Indeed, in our modelling framework, all results with anti-TNF drugs were inadequate to entirely suppress the inflammation phenotype, suggesting that blocking TNF alone is insufficient to hamper the signal. Our results also follow the findings of (Miagoux et al , 2021), which demonstrated that IL6 suppression was more successful in downregulating key transcription factors leading to inflammation in patients treated with anti-TNF treatment.…”
Section: Resultssupporting
confidence: 90%
“…• creating computational models based on disease maps, for example for rheumatoid arthritis [16,17] and atherosclerosis [15]; • creating causal-interaction networks based on a disease map [68];…”
Section: Applying the Resourcementioning
confidence: 99%
“…However it has been suggested that accounting for stochasticity within RA may be key in understanding the evolution of the disease[24, 28] and predicting the success of RA treatments [26]. Along with the stochastic models described in Section 1.2.1, a small number of studies have considered probabilistic Boolean network models for RA [65, 104].…”
Section: Introductionmentioning
confidence: 99%